Framing of Climate Change in South Asian Print Media: A Content Analysis - Javed, Muhammad Javed (Journal of Peace, Development and Communication, 2022)
Climate change is no longer only a possibility; it has become a fact. South Asia is expected to be one of the most impacted regions by global warming and climate change due to geophysical circumstances and socioeconomic and demographic backwardness. The area is home to around 1.5 billion people and a significant portion of the world’s poor.This study examines how South Asian print media framing this issue and which is the dominant frame for highlighting the issue. Framing theory is used for analysis. The news stories related to climate change published in South Asian newspapers during the year 2018 are included for analysis. The finding shows that the most frequently occurring frame in news stories was responsibility, followed by economic consequences, conflict, human interest, and morality. This study is helpful for the authorities of countries and media houses for revising and establishing the policies regarding climate change. In further studies can be conducted on how electronic media framing this issue.